Association Between Menopausal Estrogen-Only Therapy and Ovarian Carcinoma Risk. Issue 5 (May 2016) - Lee, Alice W.; Ness, Roberta B.; Roman, Lynda D.; Terry, Kathryn L.; Schildkraut, Joellen M.; Chang-Claude, Jenny; Doherty, Jennifer A.; Menon, Usha; Cramer, Daniel W.; Gayther, Simon A.; Risch, Harvey; Gentry-Maharaj, Aleksandra; et al.
Abstract : OBJECTIVE: To describe the association between postmenopausal estrogen-only therapy use and risk of ovarian carcinoma, specifically with regard to disease histotype and duration and timing of use. METHODS: We conducted a pooled analysis of 906 women with ovarian carcinoma and 1, 220 women in a control group; all 2, 126 women included reported having had a hysterectomy. Ten population-based case–control studies participating in the Ovarian Cancer Association Consortium, an international consortium whose goal is to combine data from many studies with similar methods so reliable assessments of risk factors can be determined, were included. Self-reported questionnaire data from each study were harmonized and conditional logistic regression was used to examine estrogen-only therapy's histotype-specific and duration and recency of use associations. RESULTS: Forty-three and a half percent of the women in the control group reported previous use of estrogen-only therapy. Compared with them, current or recent estrogen-only therapy use was associated with an increased risk for the serous (51.4%, odds ratio [OR] 1.63, 95% confidence interval [CI] 1.27–2.09) and endometrioid (48.6%, OR 2.00, 95% CI 1.17–3.41) histotypes. In addition, statistically significant trends in risk according to duration of use were seen among current or recent postmenopausal estrogen-only therapy users for both ovarian carcinoma histotypes ( P trend <.001 for serous and endometrioid). Compared with women in the control group, current or recent users for 10 years or more had increased risks of serous ovarian carcinoma (36.8%, OR 1.73, 95% CI 1.26–2.38) and endometrioid ovarian carcinoma (34.9%, OR 4.03, 95% CI 1.91–8.49). CONCLUSION: We found evidence of an increased risk of serous and endometrioid ovarian carcinoma associated with postmenopausal estrogen-only therapy use, particularly of long duration. These findings emphasize that risk may be associated with extended estrogen-only therapy use. Abstract : Supplemental Digital Content is Available in the Text.Menopausal estrogen-only therapy use is significantly associated with increased risk of serous and endometrioid ovarian carcinomas, especially among current, long-term users.